Constructing Interfacial Energy Transfer for Photon Up‐ and Down‐Conversion from Lanthanides in a Core–Shell Nanostructure. (5th July 2016) - Zhou, Bo; Tao, Lili; Chai, Yang; Lau, Shu Ping; Zhang, Qinyuan; Tsang, Yuen Hong
Abstract: We report a new mechanistic strategy for controlling and modifying the photon emission of lanthanides in a core–shell nanostructure by using interfacial energy transfer. By taking advantage of this mechanism with Gd 3+ as the energy donor, we have realized efficient up‐ and down‐converted emissions from a series of lanthanide emitters (Eu 3+, Tb 3+, Dy 3+, and Sm 3+ ) in these core–shell nanoparticles, which do not need a migratory host sublattice. Moreover, we have demonstrated that the Gd 3+ ‐mediated interfacial energy transfer, in contrast to energy migration, is the leading process contributing to the photon emission of lanthanide dopants for the NaGdF4 @NaGdF4 core–shell system. Our finding suggests a new direction for research into better control of energy transfer at the nanometer length scale, which would help to stimulate new concepts for designing and improving photon emission of the lanthanide‐based luminescent materials.